Caribbean interfaces - Hulst, Lieven d' (Text (Rodopi (Firm)), 2007)
Contemporary research on Caribbean literature displays a rich variety of themes, literary and cultural categories, forms, genres, languages. Still, the concept of a unified Caribbean literary space remains questionable, depending upon whether one strictly limits it to the islands, enlarges it to adopt a Latin-American perspective, or even grants it inter-American dimensions. This book is an ambitious tentative to bring together specialists from various disciplines: neither just French, Spanish, English, or Comparative studies specialists, nor strictly "Caribbean literature" specialists, but also theoreticians, cultural studies scholars, historians of cultural translation and of intercultural transfers. The contributions tackle two major questions: what is the best possible division of labor between comparative literature, cultural anthropology and models of national or regional literary histories? how should one make use of "transversal" concepts such as: memory, space, linguistic awareness, intercultural translation, orature or hybridization? Case studies and concrete projects for integrated research alternate with theoretical and historiographical contributions. This volume is of utmost interest to students of Caribbean studies in general, but also to anyone interested in Caribbean literatures in Spanish, English and French, as well as to students in comparative literature, cultural studies and transfer research